EKUITAS MEREK PRODUK KOSMETIK WARDAH DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KOTA MATARAM - Hengki Samudra (Valid: Jurnal Ilmiah, 2016)
This research entitles the "Influence of Brand awareness and brand loyalty top-rated To Consumer Decision In Buying Product of Cosmetic Wardah in Mataram City". This research Target is to know the assessment of consumer at Mataram City for Brand awareness and brand loyalty top-rated owned by-product of cosmetic Wardah and to know the influence of brand of the product of cosmetic Wardah to the decision of consumer purchasing in Mataram City. This research represents the type of research of asosiatif eksplorasi, method of data collecting used is the method of sample survey by means of data collecting in the form of the questionnaire allowed to 100 responder people, with the technique of intake sample in the form of accidental sampling. Analyzer used is Doubled Linear Regression. Result of analysis proves that variable of the dimension of brand awareness, impressive and brand loyalty top-rated by the consumer of product of cosmetic Wardah in Mataram City. All variable have an effect on by significant to consumer decision in doing purchasing of Wardah cosmetic of either through parsial and also simultan. Assess the coefficient of regression of variable of Brand Awareness (X1) of equal to 0,358 indicating that variable of Brand Awareness represents the dominant variable influence the consumer decision buy the product Wardah. Assess the R square of equal to 0,866 indicating that ability of variable of Brand Awareness (X1) and Brand loyalty (X2) in explaining variable of consumer decision buy the product Wardah is equal to 86,6%, while the rest 13,4% explained by other dissimilar variables outside research model which input do not in the research model